High-grade liver injury: outcomes with a trauma surgery–liver surgery collaborative approach - J Wallis Marsh; Abhinav Humar; Jason L Sperry; David A Geller; Deepika Mohan; Timothy R Billiar; Juan Carlos Puyana; Brian Zuckerbraun; Joshua B Brown; Matthew D Neal; Matthew R Rosengart; David Newhouse; et al. (Trauma Surgery & Acute Care Open)
Background Operative mortality for high-grade liver injury (HGLI) remains 42% to 66%, with near-universal mortality after retrohepatic caval injury. The objective of this study was to evaluate mortality and complications of operative and nonoperative management (OM and NOM) of HGLI at our institution, characterized by a trauma surgery–liver surgery collaborative approach to trauma care.Methods This was an observational cohort study of adult patients (age ≥16) with HGLI (The American Association for Surgery of Trauma (AAST) grades IV and V) admitted to an urban level I trauma center from January 2010 to November 2021. Data were obtained from the electronic medical record and state trauma registry. Patients were categorized by management strategy: immediate OM or planned NOM. The primary outcome was 30-day mortality.Results Our institution treated 179 patients with HGLI (78% blunt, 22% penetrating); 122 grade IV (68%) and 57 grade V (32%) injuries. All abdominal gunshot wounds and 49% of blunt injuries underwent initial OM; 51% of blunt injuries were managed initially by NOM. Procedures at the initial operation included hepatorrhaphy±packing (66.4%), nonanatomic resection (5.6%), segmentectomy (9.3%), and hepatic lobectomy (7.5%). Thirty-day mortality in the OM group was substantially lower than prior reports (23.4%). Operative mortality attributable to the liver injury was 15.7%. 19.4% of patients failed NOM with one death (1.4%).Conclusion We report an operative mortality of 23.4% for HGLI in a trauma care system characterized by a collaborative approach by trauma surgeons and liver surgeons.Level of evidence III